Buying Votes vs. Supplying Public Services : Political Incentives to Under-invest in Pro-poor Policies - Khemani, Stuti (World Bank, Washington, DC, 2013)
This paper uses unique survey data to provide, for the first time in the literature, direct evidence that vote buying in poor economies is associated with lower provision of public services that disproportionately benefit the poor. Various features of the data and the institutional context allow the interpretation of this correlation as the equilibrium policy consequence of clientelist politics, ruling out alternate explanations (such as, for example, poverty driving both vote buying and health outcomes). The data come from the Philippines, a country context that allows for measuring vote buying during elections and services delivered by the administrative unit controlled by winners of those elections. The data reveal a significant, robust negative correlation between vote buying and the delivery of primary health services. In places where households report more vote buying, government records show that municipalities invest less in basic health services for mothers and children; and, quite strikingly, as a summary measure of weak service delivery performance, a higher percentage of children are severely under-weight.